An acceptable time - Engle, Madeleine L (New York Square Fish, 1989)
Polly's stay with her grandparents in Connecticut becomes an extraordinary experience as she encounters old friends and mysterious strangers and finds herself traveling back in time to play a crucial role in a prehistoric confrontation
Includes an interview with the author and a genealogical table of the Murry-O'Keefe and Austin families and lists the books in which they appear
Keywords: Tham khảo